Empirical evidence regarding the impact of economic growth and inflation on economic sentiment and household consumption - Larissa Batrancea (Journal of Risk and Financial Management, 2021)
The dynamics of the interconnected global market and consumption behavior has recently changed considerably. Using a sample of 28 nations within the European Union, the study examined the degree to which economic growth and inflation impacted economic sentiment and household consumption during the time frame of December 2019 up to October 2020. The results estimated via panel generalized method of moments and panel least squares (with cross-section weights, time fixed effects) showed that economic sentiment and household consumption were significantly shaped by the proxies of economic growth and inflation. Moreover, in the case of economic sentiment, the negative impact of inflation was much stronger than the positive impact of economic growth. The reverse applied in the case of household consumption. The study draws policy implications regarding the strategies that public authorities, companies, and individual consumers could apply for stimulating national economies amid challenging times.
Keywords: 330; economic growth; economic sentiment; household consumption; inflation; unemployment